Learning Quality Improvement Management Model for Elementary School Teachers - Nisa, Choirun; Khoirurrosyid, Muhammad (JURNAL AL-TANZIM, 2023)
This paper aims to describe; 1) the weaknesses and strengths of learning in SD Muhammadiyah based on the challenges of technological disruption, 2) the need for teachers to improve the quality of learning, 3) the management model for improving the quality of learning that is appropriate to be applied by teachers in schools. This study uses a Research & Development design containing three main elements: 1) development model, 2) development procedure, and 3) product trial design. The development procedure goes through three stages: 1) preliminary study, 2) model development, and 3) model testing. The research results found that; 1) the weaknesses and strengths of learning at Muhammadiyah Elementary School, namely the quality of teachers is still lacking, the evaluation implementation is minimal; the design has not been implemented, the learning process is still lacking, and students lack motivation. In contrast, IT-based learning in schools has yet to be implemented. 2) Improving the quality of schools requires proper management based on the needs and challenges of the school going forward; teachers need learning modules, classifying student subject matter according to potential, and participatory learning.